Mahasiswa Universitas Sunan Giri & Pemerintah Sebagai Penggerak Kepedulian Lingkungan: Penelitian - Mufaizah Mufaizah; Muhammad Ilham Ihsan; Rahayu Mardikaningsih; Didi Darmawan; Asnal Mala (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The environmental cleaning activity on Jln. Brigjend Katamso shows that collaboration between students of Sunan Giri University Surabaya, the government, and the community is able to create significant positive changes in efforts to maintain the cleanliness and quality of the environment. Through the Asset Based Community Development (ABCD) approach, local potential is successfully optimized so that people are not only involved in physical activities to clean the environment, but also experience increased social awareness, solidarity, and a sense of belonging to public spaces. The results of this activity can be seen from the formation of new behaviors that are more concerned about the environment. Strengthening the culture of mutual cooperation, as well as the emergence of citizens' initiatives to continue the cleanliness program independently. These findings confirm that multistakeholder synergy is the key to success in realizing sustainable social change. So that it will always be a community that cares about the surrounding environment.